2000
DOI: 10.1046/j.1365-2508.2000.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic tube hysterectomy: a safer option?

Abstract: Objective  To compare outcomes in women undergoing total laparoscopic hysterectomy performed with the assistance of a colpotomizing tube (TLTH), with those in women in whom a laparoscopically assisted hysterectomy (LAH) procedure was performed. Design  A retrospective review of consecutive patients. Setting  State health service patients were treated at Flinders Medical Centre, Adelaide, South Australia, and private patients were treated by the same surgeons in three private hospitals in metropolitan Adel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…3,4 Proponents of the procedure, however, have gained sufficient experience that this is currently their preferred technique for hysterectomy. 5,6 A meta-analysis of 27 randomized trials indicated that the advantages of laparoscopic gynecologic surgery over abdominal include: decreased pain, fewer surgical site infections, shorter hospital stay, quicker return to activity, and a lower incidence of postoperative adhesions. 7 Although the complications of TLH have been described several times, many of these studies were limited to TLH for specific indications.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Proponents of the procedure, however, have gained sufficient experience that this is currently their preferred technique for hysterectomy. 5,6 A meta-analysis of 27 randomized trials indicated that the advantages of laparoscopic gynecologic surgery over abdominal include: decreased pain, fewer surgical site infections, shorter hospital stay, quicker return to activity, and a lower incidence of postoperative adhesions. 7 Although the complications of TLH have been described several times, many of these studies were limited to TLH for specific indications.…”
Section: Introductionmentioning
confidence: 99%
“…Proponents have gained so much experience that it is currently their preferred technique for hysterectomy. [4][5][6] The sub-classification of laparovaginal hysterectomy is dependent on the method of securing and dividing the uterine artery. 7 Laparoscopic hysterectomy (LH) refers to the laparoscopic division of the uterine vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic hysterectomy has been associated with a higher rate of ureteric injury than open and vaginal hysterectomy 1 . The practice of screening cystoscopy following laparoscopic hysterectomy has become widespread, 2,3 with the aim of improving patient outcomes by the early diagnosis and treatment of ureteric injuries. However, cases of normal findings on cystoscopic examination with subsequent detection of ureteric injuries 4 have caused concern and raised doubt about the value of screening cystoscopy in this context.…”
Section: Introductionmentioning
confidence: 99%